Manajemen Kurikulum MTS N I Lombok Timur dalam Meningkatkan Kepuasan Pelanggan Tahun Pelajaran 2018/2019 - Fadma Rosita (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this research is to know how the management of early childhood curriculum in Primagama Creative PG Kindergarten observed from aspects of: curriculum planning, curriculum organization, school and class level curriculum implementation, and curriculum evaluation. This research uses descriptive qualitative research type, with research subjects are teacher, principal, expert staff, and parents of students KB Creative Kindergarten Primagama academic year 2017/2018. The results showed that: 1) curriculum planning is done by academic creative team led by manager of PSDM. The academic creative team consists of teachers representing each level in each branch. The curriculum is designed based on the development of the curriculum set by the government that is the curriculum 2013. 2) organizing the curriculum is done by the manager of the PSDM by selecting the human resources viewed from the competence and ability of each individual. 3) the implementation of the curriculum is done well. Teachers are very categorical in carrying out the curriculum. Teachers work together to implement school-level and class-level curricula. Implementation is on schedule and according to the curriculum. 4) curriculum evaluation has been done well. From the evaluation evaluation, there is still a need for revise or perfection of the curriculum because it is still in the 2013 curriculum trial stage. Curriculum replacement for now is not necessary. 5) the inhibiting factor in the curriculum implementation is the difficulty in presenting the media from the natural materials during learning. Characteristics of developing children make teachers difficult in conditioning the class and deliver the material. Factors supporting the implementation of the curriculum in the availability of sufficient funds, facilities and complete infrastructure, and good human resources capabilities. 6) the level of customer satisfaction in the academic year 2017/2018 has been achieved with the implementation of curriculum management at the Primagama Kindergarten Kindergarten.